MENGATASI PERILAKU KONTRAPRODUKTIF APARATUR NEGARA MELALUI SISTEM REMUNERASI (SEBUAH REVIEW MENGENAI KEADILAN ORGANISASI) - Winurini, Sulis (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2014)
The purpose of this study is to evaluate the implementation of remuneration system in bureaucracy reform, with reference to organizational justice theory. Research methodology used was literature review. The study concluded that there was a real effort by the government to implement fairness principle in remuneration package, as part of bureaucracy reform. The implementation of fairness principles is captured in consideration of employees’ contribution to determine the performance benefit value. However, further restructuring process of remuneration system is still needed. Contribution is still emphasizing on discipline rather than work performance to determine the performance benefit values. Furthermore, there was also a problem of budget allocation for remuneration package. Ideal benefit payment for employees is still difficult to reach within this decade. Harmonization between strategy and employees’ response needs to be continuously diagnosed due to different characteristic of bureaucracy in various governmental bodies. The implementation of fairness principles in remuneration system is just one of the strategies to fight against counterproductive behavior. Support on other strategies is still needed in order to reach optimum condition of the remuneration system, as expected.